'Second' Ehrenfest equation for second order phase transition under hydrostatic pressure. Issue 6 (21st February 2018) - Moin, Ph. B.
Abstract: It is shown that the fundamental conditions for the second-order phase transitions and, from which the two Ehrenfest equations follow (the 'usual' and the 'second' ones), are realised only at zero hydrostatic pressure ( ). At the volume jump Δ V at the transition is proportional to the pressure and to the jump of the compressibility Δ ζ V, whereas the entropy jump Δ S is proportional to the pressure and to the jump of the thermal expansion coefficient Δ α V . This means that at non-zero hydrostatic pressure the phase transition is of the first order and is described by the Clausius–Clapeyron equation. At small pressure this equation coincides with the 'second' Ehrenfest equation . At high P, the Clausius–Clapeyron equation describes qualitatively the caused by the crystal compression positive curvature of the dependence.